Structural, Morphological, Magneto-Transport and Thermal Properties of Antimony Substituted (La,Pr)2/3Ba1/3Mn1-xSbxO3 Perovskite Manganites - Panwar, Neeraj; Coondoo, Indrani; Sen, Vikram; Agarwal, S. K. (IntechOpen, 2011)
None